Implementasi Sistem Informasi Sekolah Terpadu Berbasis Web pada Pusat Kegiatan Belajar Mengajar (PKBM) di Jawa Barat - Hapsari Widyani (NUCLEUS, 2020)
The purpose of this study is to assist the teaching and learning process of administrative services and financial reporting in community learning activity centers with a well-integrated system. The data used are primary data. The data collection method used is direct observation on the research object, namely PKBM Patrakomala and PKBM Hiama. The method of analysis is descriptive qualitative analysis with the design based on web technology and MySQL for the database. The results in this study are that administrative services and financial reporting at PKBM use a well-integrated system so as to produce accountable and accurate financial reporting.